2012
DOI: 10.1111/j.1365-2966.2012.22025.x
|View full text |Cite
|
Sign up to set email alerts
|

A deep, wide-field study of Holmberg II with Suprime-Cam: evidence for ram pressure stripping

Abstract: We present a deep, wide-field optical study of the M81 group dwarf galaxy Holmberg II (HoII) based on Subaru/Suprime-Cam imaging. Individual stars are resolved down to I ∼ 25.2, that is, about 1.5 mag below the tip of the red giant branch (RGB). We use resolved star counts in the outskirts of the galaxy to measure the radial surface brightness profile down to μ V ∼ 32 mag arcsec −2 , from which we determine a projected exponential scalelength of 0.70 ± 0.01 arcmin (i.e. 0.69 ± 0.01 kpc). The composite profile,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 67 publications
(87 reference statements)
1
22
0
Order By: Relevance
“…The morphology of atomic hydrogen in this galaxy is extremely inhomogeneous. The observed large-scale cometlike asymmetry of the H i disc is probably caused by the ram pressure stripping due to the hot intragroup medium (Bernard et al 2012). The H i distribution in the galaxy Oh et al (2011) c Updated Local Volume galaxies database (Karachentsev et al 2013, http://www.sao.ru/lv/lvgdb/) d Moustakas et al (2010) e Sánchez-Salcedo et al (2014) disc represents a large number of contiguous giant supershells and 'holes' (most representable of them are shown in Fig.…”
Section: Multi-wavelength Overview Of Holmberg IImentioning
confidence: 99%
“…The morphology of atomic hydrogen in this galaxy is extremely inhomogeneous. The observed large-scale cometlike asymmetry of the H i disc is probably caused by the ram pressure stripping due to the hot intragroup medium (Bernard et al 2012). The H i distribution in the galaxy Oh et al (2011) c Updated Local Volume galaxies database (Karachentsev et al 2013, http://www.sao.ru/lv/lvgdb/) d Moustakas et al (2010) e Sánchez-Salcedo et al (2014) disc represents a large number of contiguous giant supershells and 'holes' (most representable of them are shown in Fig.…”
Section: Multi-wavelength Overview Of Holmberg IImentioning
confidence: 99%
“…Color-magnitude diagrams are a widely used tool to study the stellar fossil records of nearby galaxies (Monelli et al (2010), Rubele et al (2011), Bernard et al (2012. This approach is currently limited to the local Universe, for which resolved photometric data is accessible with the currently available instruments.…”
Section: Constructing Realistic Color-magnitude Diagramsmentioning
confidence: 99%
“…These five illustrative examples provide a direct grasp of our ability in resolving individual stars as a function of galaxy distance. Previous studies have demonstrated that individual RGB stars can be resolved from the ground in the least crowded galaxy outskirts up to distances of ∼4-5 Mpc, provided that the seeing is as good as 0.8 (e.g Bernard et al 2012;Okamoto et al 2015;Crnojević et al 2016). The CMDs obtained from our analysis confirm these results, showing that RGB stars, tracing the underlying old (>1-2 Gyr) stellar population, are reached up to targets at D 5 Mpc, while only brighter stellar phases (young main sequence stars, blue and red supergiants, asymptotic giant branch stars) are accessible at larger distances.…”
Section: Color-magnitude Diagramsmentioning
confidence: 99%
“…The CMDs presented in section 7 provide a powerful diagnostic to separate stars belonging to the target galaxies from background and foreground contaminants. This technique has been extensively used in the literature to identify low surface brightness stellar streams, satellites, and extended stellar halos in galaxies within the Local Group and beyond (e.g., Belokurov et al 2006;Bernard et al 2012;Bonaca et al 2012;Beccari et al 2014;Greggio et al 2014;Martin et al 2014;Roderick et al 2015;Belokurov & Koposov 2016;Crnojević et al 2016;Higgs et al 2016;Mackey et al 2016;Tanaka et al 2017;McConnachie et al 2018;Pucha et al 2019). This approach allows to typically reach much fainter surface brightness structures than from the integrated light, down to values as low as 31-35 mag arcsec −2 , depending on the faintest evolutionary phase sampled by the CMD.…”
Section: Stellar Density Mapsmentioning
confidence: 99%